Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve for [tex]\( h \)[/tex] in the equation [tex]\(0.0027 = 2.7 \times 10^h\)[/tex], we can follow these steps:
1. Isolate the exponential term [tex]\( 10^h \)[/tex]:
Begin by dividing both sides of the equation by 2.7 to isolate the [tex]\( 10^h \)[/tex] term.
[tex]\[ \frac{0.0027}{2.7} = \frac{2.7 \times 10^h}{2.7} \][/tex]
Simplifying the right-hand side, we get:
[tex]\[ \frac{0.0027}{2.7} = 10^h \][/tex]
2. Simplify the fraction:
Calculate the value of the fraction:
[tex]\[ \frac{0.0027}{2.7} = 0.001 \][/tex]
Therefore, the equation becomes:
[tex]\[ 0.001 = 10^h \][/tex]
3. Convert to logarithmic form:
To solve for [tex]\( h \)[/tex], take the base-10 logarithm (logarithm to base 10) of both sides:
[tex]\[ \log_{10}(0.001) = \log_{10}(10^h) \][/tex]
Using the logarithm property [tex]\( \log_{10}(10^h) = h \)[/tex]:
[tex]\[ \log_{10}(0.001) = h \][/tex]
4. Evaluate the logarithm:
Recall that [tex]\( 0.001 = 10^{-3} \)[/tex]. Therefore:
[tex]\[ \log_{10}(10^{-3}) = -3 \][/tex]
So, [tex]\( h \)[/tex] is:
[tex]\[ h = -3 \][/tex]
Therefore, the value of [tex]\( h \)[/tex] in the equation [tex]\( 0.0027 = 2.7 \times 10^h \)[/tex] is [tex]\(-3\)[/tex].
1. Isolate the exponential term [tex]\( 10^h \)[/tex]:
Begin by dividing both sides of the equation by 2.7 to isolate the [tex]\( 10^h \)[/tex] term.
[tex]\[ \frac{0.0027}{2.7} = \frac{2.7 \times 10^h}{2.7} \][/tex]
Simplifying the right-hand side, we get:
[tex]\[ \frac{0.0027}{2.7} = 10^h \][/tex]
2. Simplify the fraction:
Calculate the value of the fraction:
[tex]\[ \frac{0.0027}{2.7} = 0.001 \][/tex]
Therefore, the equation becomes:
[tex]\[ 0.001 = 10^h \][/tex]
3. Convert to logarithmic form:
To solve for [tex]\( h \)[/tex], take the base-10 logarithm (logarithm to base 10) of both sides:
[tex]\[ \log_{10}(0.001) = \log_{10}(10^h) \][/tex]
Using the logarithm property [tex]\( \log_{10}(10^h) = h \)[/tex]:
[tex]\[ \log_{10}(0.001) = h \][/tex]
4. Evaluate the logarithm:
Recall that [tex]\( 0.001 = 10^{-3} \)[/tex]. Therefore:
[tex]\[ \log_{10}(10^{-3}) = -3 \][/tex]
So, [tex]\( h \)[/tex] is:
[tex]\[ h = -3 \][/tex]
Therefore, the value of [tex]\( h \)[/tex] in the equation [tex]\( 0.0027 = 2.7 \times 10^h \)[/tex] is [tex]\(-3\)[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.